METHODOLOGY FOR INTEGRATED TRAINING OF SPECIALISTS IN THE SPACE OF CONTINUOUS SPECIALIZED EDUCATION (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
This article scientifically substantiates the methodology for integrated training of specialists within the Continuous Specialized Vocational Education (CSVE) space. The study examines in detail the purpose of the CSVE space modeling and creation methodology, its fundamental principles, and three directions of organizational-pedagogical conditions: vertical, horizontal, and parallel integration models. The structure, goals, expected outcomes, and performance indicators for each integration model are presented. Furthermore, a training model based on an individual educational trajectory and its structural components - professional-content, directing, regulatory-control, and motivational components of the educational route - are described. Research findings scientifically confirm the effectiveness of integrated training within the CSVE space and its significant role in the professional development of specialist-educators.